Effect of concentration and temperature of osmotic solution on mass transfer kinetics and its influence on quality of aonla (Emblica officinalis) segments - KUMAR, P SURESH; SAGAR, V R (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted to find out the optimum osmotic concentration and temperature for the preparation of osmo-vac dehydrated aonla segments. Blanched segments were dipped in various sugar concentration, viz. 400B, 500B, 600B and 700B with the temperature viz., 40°C, 50°C, 60°C and 70°C for six hours without any agitation. At the end of osmosis, segments were analyzed for various quality parameters and sensory attributes. It was indicated that water loss (WL) and solid gain (SG) increased with the increase in sugar concentrations and temperatures of the solution during osmosis process. The regression analysis showed that the process variables have significant effect on osmosis. Sensory attributes revealed that 60° B sugar concentration with 60°C temperature gave better results than the rest of the treatments.